2018
DOI: 10.1177/0284185118758132
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic screening attendance among immigrant and minority women: a systematic review and meta-analysis

Abstract: Background Groups of immigrant and minority women are more often diagnosed with advanced stage breast cancer than other women. Mammographic screening aims to reduce mortality from breast cancer through early detection in asymptomatic women. Purpose To compare mammographic screening attendance among immigrant and minority women to that of other women. Material and Methods A literature search of PubMed, Embase, Google Scholar, and Cochrane identified 1369 papers published between January 1995 and March 2016. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 30 publications
5
35
0
Order By: Relevance
“…The study was part of a larger research project using several different approaches to investigate breast cancer and breast cancer screening attendance among immigrant women. So far, the project has demonstrated that immigrant and minority women have lower attendance rates than other women across the world (20), that this is the case also in Norway, both overall and for all levels of all sociodemographic factors studied (3,5), and that mammographic screening performance measures differ between immigrants and non-immigrants in Norway (21).…”
Section: Methodsmentioning
confidence: 99%
“…The study was part of a larger research project using several different approaches to investigate breast cancer and breast cancer screening attendance among immigrant women. So far, the project has demonstrated that immigrant and minority women have lower attendance rates than other women across the world (20), that this is the case also in Norway, both overall and for all levels of all sociodemographic factors studied (3,5), and that mammographic screening performance measures differ between immigrants and non-immigrants in Norway (21).…”
Section: Methodsmentioning
confidence: 99%
“…In general, the reviews that concluded on questionable impact of socio-economic determinants were older (searched before 2003) and relied on both crosssectional and prospective studies, whereas the positively framed reviews were based on more recent crosssectional evidence. 14,15,23,24 Intentions to screening was the only consistent patient's predisposing factor associated with BCS attendance (Table 1). 14,15 Physician predisposing factors (demographics, gender, ethnicity, language, beliefs, attitudes, prior clinical experience, and personal health practices) were not reported in the summarized literature.…”
Section: Factors Contributing To Variability In Bcs Participation Andmentioning
confidence: 98%
“…Public cancer screening programs using mammography and the Papanicolaou (Pap) test have successfully decreased breast and cervical cancer mortality in Western countries over the past decades . However, ethnic minority women have low participation rates in breast and cervical cancer screening in the United States, Europe, Canada, and Australia . Cancer causes extreme suffering for each woman and her family.…”
Section: Introductionmentioning
confidence: 99%